Z czego był dumny Halikarnas? - Szastyńska-Siemion, Alicja (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The article presents and analyses the newly-found anonymous inscriptional elegiac poem on ancient Halikarnassos and his reasons of pride.
What was Halikarnassos pro ud of?
Keywords: Halikarnassos; foundation myths; Aphrodite; Hermaphroditus; Salmacis; poets and writers of the city